Isolation and expression analysis of transcripts encoding metallothioneins in oil palm - Al-Shanfari, Ahmed Bakhit; Abdullah, Siti Nor Akmar (Springer Netherlands, 2014)
Two of the abundant transcripts encoding type 2 metallothionein (MT) proteins designated as MET2a and MET2b were selected in our previous study due to their high abundance (16.05 %) in the suppression subtractive hybridization library and their involvement in fruit development and maturation. The present study involves the isolation of the full-length cDNA encoding MET2a and MET2b from the ripening oil palm fruit mesocarp, examining their expression pattern compared to the other two previously reported type-3 MT members (MT3-A and MT3-B) in various oil palm organs including different vegetative and reproductive tissues. The full-length cDNA sequences of MET2a and MET2b were 571 and 553 bp and they were designated as EgMT2a and EgMT2b, respectively. The sequences of the EgMT2a and EgMT2b were then compared for sequence similarities in the database using both BLASTN and BLASTX programs. Their sequences were homologous (67–77 %) with several type-2 MTs in plants. All four MT encoding genes were differentially expressed in the ripening oil palm mesocarp tissues, but undetectable in the vegetative tissues examined. All MT genes examined were significantly up-regulated in the mature developmental stages of oil palm fruit mesocarp, except for EgMT2b which was expressed only at 17 weeks after anthesis. The type 2 MT proteins are related to a greater degree to the late fruit-ripening stage than the type 3 MT proteins consistent with their reported functions in homeostasis or detoxification. The findings in the present study contribute to better understanding the molecular mechanisms involved in fruit ripening in oil palm.